Defective MWCNT Enabled Dual Interface Coupling for Carbon‐Based Perovskite Solar Cells with Efficiency Exceeding 22%. (14th May 2022) - Wang, Yudi; Li, Wenrui; Yin, Yanfeng; Wang, Minhuan; Cai, Wanxian; Shi, Yanying; Guo, Jingya; Shang, Wenzhe; Zhang, Chunyang; Dong, Qingshun; Ma, Hongru; Liu, Jing; et al.
Abstract: Suffering from sluggish charge transfer kinetics, carbon‐based perovskite solar cells (C‐PSCs) lag far behind the Ag/Au‐based normal PSCs in power conversion efficiency (PCE). Herein, the use of defective multi‐walled CNT (D‐MWCNT) is demonstrated to tune the charge transfer kinetics regarding hole transport layer (HTL) and the interface between HTL and carbon electrode. Benefiting from the electrostatic dipole moment interaction between the terminal oxygen‐containing groups of D‐MWCNT and 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐p‐methoxyphenylamine)‐9, 9′‐spirobifluorene, an interface coupling at molecular level is established and in turn, allows rapid charge transfer by edge effect induced electron redistribution and 1D hyper‐channels. Meanwhile, a seamless connection between HTL and carbon electrode is achieved in a novel modular C‐PSCs due to D‐MWCNT induced interface coupling with graphene at nanometer scale. Based on this strategy, high PCEs up to 22.07% (with a certified record PCE of 21.9% to date for C‐PSCs) and excellent operational stability have been achieved. Abstract : Dual interface coupling is established by defective multi‐walled carbon nanotube to well tune the charge transfer kinetics regarding hole transport layer (HTL) itself at molecular level and the interface between HTL and carbon electrode at nanometer scale. High power conversion efficiency (PCEs) up to 22.07% (with a certified PCE of 21.9%) and excellent operational stability are achieved.